Niger : Requests for Disbursement Under the Rapid Credit Facility and for Rephasing of Access Under the Extended Credit Facility -Press Release; Staff Report; and Statement by the Executive Director for Niger. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Niger's Requests for Disbursement Under the Rapid Credit Facility and for Rephasing of Access Under the Extended Credit Facility. The coronavirus disease 2019 (COVID-19) pandemic is inflicting significant damage on Niger's economy at a time when the government is already faced with the deteriorating security situation across the Sahel region. A first local infection was reported on March 19, 2020 and a state of emergency was declared on March 27, 2020. The authorities adopted a comprehensive response plan, comprising health care measures and steps to alleviate the social and economic fallout from the crisis. The 5th program review was concluded on January 8, 2019. Performance has since been mixed. Difficulties to reliably recalibrate program parameters while the global COVID-19 crisis is still unfolding preclude the conduct of the 6th program review on the regular schedule. As a result, the authorities previously requested an extension of the program and now request rephasing the final disbursement due to the delay.